Global health concern of cyanotoxins in surface water and its various detection methods - Ramya, M.; Umamaheswari, A.; Elumalai, S. (Current Botany, 2020)
Water is an absolutely required resource for life nourishment especially for the purpose of drinking, domestic and farming. People in various part of the world are under prodigious threat due to unenviable changes in the physical-chemical and biological properties of an ecosystem. Due to anthropogenic causes like industrialization, the use of fertilizers and urbanization leads to highly polluted water bodies that include fresh and brackish water. These changes influence the harmful growth of cyanobacteria that is blue green algae. cyanoHABs (Cyanobacterial Harmful Algal Blooms) became a worldwide threat to drinking and recreational purpose due to its adopting nature according to the temperature fluctuations. In this study, a basic introduction to cyanotoxins as well as the entanglement of public health that includes route of exposure health effects and the pervasive impact of cyanotoxins and alleviation efforts in the waterbodies along with that the toxicosis. Cyanobacterial toxins such as hepatotoxicosis, neurotoxicosis, gastrointestinal disturbances respiratory and allergic reactions were reviewed. Their detection process and the treatment techniques with various physicochemical methods and bioassay methods were also reviewed.